2002
DOI: 10.1021/la0262654
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Effect of Enzymatic Manipulation of DNA on Microcantilever Surfaces

Abstract: Microcantilevers functionalized with DNA incorporating a Hind III restriction endonuclease site were digested with Hind III to produce DNA with a single-stranded end on the cantilever surface. Ligase was then used to link a second DNA molecule with a compatible end to the DNA on the cantilever. Nanomechanical motion of the cantilever was monitored throughout the digestion and ligation. Fluorescently labeled DNA was used to confirm that ligation and digestion occurred. The DNA was attached to the silicon side b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…It has been reported that detection systems based on measuring de°ections of micro-and nanocantilevers can be applied to targets ranging from the molecular to the organismal scale, such as proteins 11,38,39 and enzymes, 13 DNA, [40][41][42] RNA, 14 bacteria, 43 viruses, 44 and volatile organic compounds. 18 Several papers showed that nanomechanical cantilevers are e±cient devices for detection at nanoscale and even in picolevels (Table 1), and can be applied in di®erent areas such as cancer or contaminants detection.…”
Section: Nanobiosensor Response To Hppd Concentrationsmentioning
confidence: 99%
“…It has been reported that detection systems based on measuring de°ections of micro-and nanocantilevers can be applied to targets ranging from the molecular to the organismal scale, such as proteins 11,38,39 and enzymes, 13 DNA, [40][41][42] RNA, 14 bacteria, 43 viruses, 44 and volatile organic compounds. 18 Several papers showed that nanomechanical cantilevers are e±cient devices for detection at nanoscale and even in picolevels (Table 1), and can be applied in di®erent areas such as cancer or contaminants detection.…”
Section: Nanobiosensor Response To Hppd Concentrationsmentioning
confidence: 99%
“…Experiments reveal that the chip deflection can arise from numerous factors, such as concentration of DNA molecules (Fritz et al, 2000), salt concentration in buffer solution (Wu et al, 2001), length and sequence of DNA molecules (Hansen and Thundat, 2005), grafting density of single-stranded DNA (ssDNA) molecules, hybridization density (Stevenson et al, 2002;Castelino et al, 2005), time, and temperature. And immobilization of endthiolated probe ssDNA molecules on the gold surface, or hybridization of ssDNA molecules can also induce tensile or compressive surface stress at different conditions.…”
Section: Introductionmentioning
confidence: 99%
“…They showed a surface stress on the order of 0.1-0.5 N/m and also reported that the magnitude of surface stress increased linearly with the carbon chain backbone of the monolayer. Since the first report by Berger et al (1997), SAMs have been used as test system for almost all cantilever based sensing techniques (Godin et al, 2004;Raiteri et al, 2000;Ji et al, 2000;Stevenson et al, 2002). This is because they are relatively easy to prepare, form well-ordered close packed films and offers limitless possibilities of variations in chain length, end group and ligand attachments (Ulman, 1991).…”
Section: Introductionmentioning
confidence: 99%